1999
DOI: 10.1163/156856199x00055
|View full text |Cite
|
Sign up to set email alerts
|

Quinone-amine polyurethanes: novel corrosion-inhibiting coupling agents for bonding epoxy to steel

Abstract: A novel series of quinone-amine polyurethanes (QAPs) were synthesized and tested for their efficiency as corrosion-inhibiting polymeric coupling agents to enhance the adhesion of epoxy to steel. These polymers were characterized using infrared spectroscopy, thermal analysis methods (TGA and DSC), tensile testing, and gel permeation chromatography. The coupling agent-treated epoxy-steel torsional joints were tested (dry and after wet environments) in shear. These joints demonstrated a 10-15% dry strength improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…These polyurethanes were shown to inhibit the corrosion of the commercial iron particles used in state‐of‐the‐art metal particle tape 10–13. We also demonstrated that amine–quinone polyurethanes promote the adhesion of epoxy to steel 14, 15…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…These polyurethanes were shown to inhibit the corrosion of the commercial iron particles used in state‐of‐the‐art metal particle tape 10–13. We also demonstrated that amine–quinone polyurethanes promote the adhesion of epoxy to steel 14, 15…”
Section: Introductionmentioning
confidence: 61%
“…The amine–quinone polyurethanes and the amine–quinone polyimides provide an opportunity to test this model. We have already shown that amine–quinone polyurethanes promote adhesion of epoxy to steel 14, 15. We speculate that the amine–quinone polymers chemisorb to the iron surface and expect that the bond strength would depend on the nature of the amine–quinone functional group and the number of groups adsorbing to the iron surface.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…4 They also promoted the adhesion of epoxy to steel. 5 Curiosity led us to explore the possibility of replacing the amine group with a thioether group. We have developed the synthesis of a sulfur-quinone diol monomer and die preparation of polyurethanes containing this sulfurquinone monomer.…”
Section: A Sulfur-quinone Diol Monomer 25-bis-(2-hydroxyethylthio)-mentioning
confidence: 99%